2006
DOI: 10.1002/prot.21146
|View full text |Cite
|
Sign up to set email alerts
|

Pump‐probe molecular dynamics as a tool for studying protein motion and long range coupling

Abstract: A new method for analyzing the dynamics of proteins is developed and tested. The method, pump-probe molecular dynamics, excites selected atoms or residues with a set of oscillating forces, and the transmission of the impulse to other parts of the protein is probed using Fourier transform of the atomic motions. From this analysis, a coupling profile can be determined which quantifies the degree of interaction between pump and probe residues. Various physical properties of the method such as reciprocity and spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
131
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 74 publications
4
131
0
Order By: Relevance
“…To obtain the missing bond parameters for the sulfonate groups, the antechamber tool was employed. 60 The side chains of all four histidine residues (33,54,72, and 87) of PDZ2S were chosen electrostatically neutral (mono-protonated). The lengths of bonds involving hydrogens were constrained, 61 allowing for a 2 fs time step.…”
Section: Methods Simulation Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the missing bond parameters for the sulfonate groups, the antechamber tool was employed. 60 The side chains of all four histidine residues (33,54,72, and 87) of PDZ2S were chosen electrostatically neutral (mono-protonated). The lengths of bonds involving hydrogens were constrained, 61 allowing for a 2 fs time step.…”
Section: Methods Simulation Set-upmentioning
confidence: 99%
“…16 The nature of the subsequent ligand-induced intramolecular signaling process, however, remains a matter of debate, although various proposals of signaling pathways exist. [30][31][32][33][34][35][36][37][38] To facilitate a dynamic perspective of the allosteric mechanism, recently Buchli et al 45 presented a time-resolved study of the transition from the free to the bound state of PDZ2 triggered by a molecular photoswitch. [46][47][48][49][50][51] By covalently linking an azobenzene photoswitch across the binding groove and using a femtosecond laser pulse that affects the cis → trans photoisomerization of azobenzene, they were able to initiate a conformational change similar to the free-bound transition.…”
Section: Introductionmentioning
confidence: 99%
“…By clustering the binding induced fluctuation profiles of a diverse set of PDZ domains, we showed that ENM predicted normal modes not only can identify the structural regions and types of correlated fluctuations critical for binding of Class I and Class II peptides but also predicts binding selectivity of PDZs. 49 The challenge of PDZ domain (i.e., the reasons behind their selectivity and promiscuity) and their link to many different diseases has led to a number of important experimental 50,51 and computational 49,[52][53][54][55][56][57][58] studies. Niv and Weinstein also developed a flexible docking scheme (called PDZDocScheme), 56 which is based on simulated annealing molecular dynamics with the soft core potential or flexible binding site side chains, followed by rotamer optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Karplus and coworkers have revealed two continuous correlation pathways in a PDZ2 domain and highlighted the existence of such pathways even in the absence of the ligand (24). A number of theoretical (23,26,27) and experimental (6, 28) studies propose multiple allosteric pathways for PDZ domains on the basis of evolutionary information (29, 30), local structural changes (22, 31, 32), heat-diffusion pathways (33, 34), and energy connectivity networks (35,36). Most of the existing approaches look for Significance Allosteric regulation is a crucial component in biochemical pathways, where ligand binding to an allosteric site modulates the enzymatic activity at a distant functional site.…”
mentioning
confidence: 99%